Behavioral economics - O'Sullivan, Arthur (New York, NY Oxford University Press, 2023)
Topical, interactive, and written at the right level, this text introduces the field of Behavioral Economics to students using a contemporary and engaging approach developed by a celebrated economist with several textbooks and over a decade's worth of academic writing experience to his name. Rather than simply listing and defining patterns of human behavior that influence the economy, Behavioral Economics utilizes cross-disciplinary data to identify these behaviors, where they stem from, why they persist, and how past attempts to control and mitigate them have strengthened or weakened the economy in the long run"--
Includes bibliographical references and index.
Keywords: Economics -- Psychological aspects